2020
DOI: 10.1053/j.gastro.2020.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Sclerosing Cholangitis on Risks of Cancer and Death in People With Inflammatory Bowel Disease, Based on Sex, Race, and Age

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
134
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(149 citation statements)
references
References 49 publications
7
134
4
4
Order By: Relevance
“…A genetic study of 186 patients with PSC-biliary tract cancer showed eCCA with high genomic alterations in TP53 (35.5%), KRAS (28.0%), CDKN2A (14.5%), and SMAD4 (11.3%), and even in underlying druggable mutation genes, such as HER2 / ERBB2 [ 32 ]. Moreover, a 10-year nationwide population-based study from the UK suggested that development of PSC increases the risk of CCAs (hazard ratio [HR] = 28.46, p < 0.001) in patients with PSC-IBD, and it also increases the risk of HCC (HR = 21.00, p < 0.001), gallbladder cancer (HR = 9.19, p < 0.001), pancreatic cancer (HR = 5.26, p < 0.001), and colorectal cancer (HR = 2.43, p < 0.001) [ 33 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…A genetic study of 186 patients with PSC-biliary tract cancer showed eCCA with high genomic alterations in TP53 (35.5%), KRAS (28.0%), CDKN2A (14.5%), and SMAD4 (11.3%), and even in underlying druggable mutation genes, such as HER2 / ERBB2 [ 32 ]. Moreover, a 10-year nationwide population-based study from the UK suggested that development of PSC increases the risk of CCAs (hazard ratio [HR] = 28.46, p < 0.001) in patients with PSC-IBD, and it also increases the risk of HCC (HR = 21.00, p < 0.001), gallbladder cancer (HR = 9.19, p < 0.001), pancreatic cancer (HR = 5.26, p < 0.001), and colorectal cancer (HR = 2.43, p < 0.001) [ 33 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The high cancer risk in PSC is well established and cancer is the most common cause of death [1,4,10] . The risk is highest for bile duct cancer, but increased risks for hepatocellular carcinoma (HCC), pancreatic cancer, and colorectal cancer (CRC) are also reported [2,[11][12][13] . Cholangiocarcinoma (CCA) has an aggressive course and poor prognosis with a one-year mortality rate of up to 80% [14] .…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, there are additional risks of hepatocellular (HR: 21.00), gallbladder (HR: 9.19), and pancreatic carcinoma (HR: 5.26). 24 A cumulative 11 to 14% 10-year risk for colorectal cancer (CRC) exists in patients with PSC-IBD. 19,22 The risk of CRC is greatest in PSC-IBD patients with pancolitis.…”
mentioning
confidence: 99%
“…24 Furthermore, the incidence of CRC among those diagnosed at age < 50 years old with PSC-IBD is fivefold greater versus those with IBD alone. 24 Thus, all patients with PSC should be assessed for concurrent IBD at initial diagnosis and those with colitis should undergo regular surveillance with annual colonoscopy. 2,26 Regular abdominal imaging to screen for gallbladder, biliary tree, and liver abnormalities is also recommended, especially in patients who develop symptom changes or worsening laboratory parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation